(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Nanocarriers have shown promise as effective delivery vehicles. Controlled release, and enhanced efficacy of therapeutics, imaging agents, and functional payloads in various applications. An overview of the synthesis processes, characterization methodologies, and uses of nanocarriers in agriculture, environmental sustainability, and healthcare is given in this abstract. Common types of nanocarriers, including liposomes, polymeric nanoparticles, dendrimers, and metal-based nanoparticles, are discussed, along with their synthesis methods and key properties. Characterization techniques such as transmission electron microscopy, dynamic light scattering, Fourier-transform infrared, and cell viability assays are highlighted for evaluating the physicochemical properties, stability, and biocompatibility of nanocarriers. Applications of nanocarriers in drug delivery, diagnostics, gene therapy, agriculture, and environmental remediation are explored, showcasing their potential to address critical challenges and improve human health and environmental sustainability. Despite their promise, nanocarriers face challenges such as biocompatibility concerns, stability issues, and regulatory considerations, necessitating interdisciplinary collaboration and rigorous safety assessments for their successful translation into practical use. Looking ahead, nanocarriers hold tremendous promise for personalized medicine, combination therapies, smart and stimuli-responsive systems, theragnostic, and sustainable solutions, shaping a future where precision, efficiency, and tailored solutions transform healthcare, agriculture, and environmental management. To fully utilize nanocarrier technology and advance science, health, and technology for the good of society, more funding, cooperation, and research will be needed.